Walter Donner with Apollo Atmosphere Analyzer System - Frey Photos (1962)
Walter Donner was the manager of Beckman Instruments' Space Engineering Department and oversaw development of medical monitoring equipment for the Apollo, Mercury, and Gemini manned spaceflight missions.
Keywords: Scientists--Portraits; Scientific apparatus and instruments; Atmosphere--Analysis; Beckman Instruments, Inc.